A Contextual Approach-Based E-Book to Improve Students' Metacognitive Abilities in Grade V Science Learning - Sitepu, Fitra; Alexander Hamonangan Simamora; Adrianus I Wayan Ilia Yuda Sukmana (Jurnal Media dan Teknologi Pendidikan, 2025)
Metacognition is the ability to understand, control, and evaluate thinking processes, which is important for independent learning, critical thinking, and adaptation in the 21st century. However, the metacognitive abilities of elementary school students are still low, as seen in their low IPAS scores due to limited teaching materials. The aim of this study is to develop a valid and effective contextual-based e-book to improve students’ metacognitive abilities. This research uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study consisted of three experts and 25 students. Data were collected in both quantitative and qualitative forms, using questionnaires for expert validation. Test instruments were used for the pretest and posttest, and data were analyzed using the t-test technique. The results showed that the e-book was successfully developed through the stages of the ADDIE model. The e-book was declared valid based on expert reviews, with a score of 96.00% from content experts, 96.00% from instructional design experts, and 98.00% from media experts. User responses to the e-book reached 98.00% in individual trials and 98.22% in small group trials. The effectiveness of the e-book, based on the t-test, showed a significance level of 0.000 < 0.05, indicating a significant difference in students’ metacognitive abilities before and after using the e-book. It can be concluded that contextual e-books are valid and effective in improving metacognitive abilities and have implications for improving students' metacognitive abilities. They are also a solution to overcome the limited teaching materials available in the learning process.